2004
DOI: 10.1203/01.pdr.0000141518.19721.d7
|View full text |Cite
|
Sign up to set email alerts
|

Infant Pulmonary Function in a Randomized Trial of Fetal Tracheal Occlusion for Severe Congenital Diaphragmatic Hernia

Abstract: Congenital diaphragmatic hernia (CDH) carries a high mortality risk secondary to pulmonary hypoplasia and respiratory failure. In experimental animals, fetal tracheal occlusion (TO) induces lung growth and morphologic maturation. We measured indicators of pulmonary function in 20 infants who were enrolled in a randomized trial of fetal TO as treatment for severe CDH [nine with conventional treatment (controls); 11 with TO]. We hypothesized that TO would improve lung function. At birth, the TO group had a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 57 publications
2
41
0
1
Order By: Relevance
“…Infants were managed with gentle ventilation, using permissive hypercapnia, pressure limitation, and permissive oxygenation (38). Details of neonatal respiratory support are available in the online data supplement.…”
Section: Neonatal Clinical Managementmentioning
confidence: 99%
“…Infants were managed with gentle ventilation, using permissive hypercapnia, pressure limitation, and permissive oxygenation (38). Details of neonatal respiratory support are available in the online data supplement.…”
Section: Neonatal Clinical Managementmentioning
confidence: 99%
“…Effects on pulmonary function of CDH patients treated with fetal TO are preliminary. Keller et al [43] [48,[59][60][61]. Bronchodilators and inhaled steroids were, at least transiently, used by the majority of CDH patients, during the first year of life and thereafter [61,62].…”
Section: Fetal Tracheal Occlusionmentioning
confidence: 99%
“…Harrison et al [42] showed in a (small) randomized controlled trial comparing fetal endoscopic TO to standard care that mortality is equal. Data concerning long-term outcomes of fetal endoscopic TO are very scarce [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, temporary fetoscopic endoluminal TO (FETO), a minimally invasive surgical technique intended for the most severely affected CDH fetuses (27), improved prenatal imaging findings (8) and neonatal survival rates (27,50). Nevertheless, only sparse functional and morphometric findings have been reported (16,24,31).…”
mentioning
confidence: 99%
“…Because mechanical ventilation and oxygen therapy are standard treatments for neonatal respiratory insufficiency, CDH survivors treated or not by FETO are at high risk of developing BPD (15,59). Despite increased lung growth, temporary TO did not noticeably improve neonatal respiratory function in human and experimental CDH (17,31). Since the underlying biological mechanisms are unknown, clarifying the status of TGF-␤ after TO might be clinically relevant.…”
mentioning
confidence: 99%